Tachycardia and persistent pulmonary hypertension of the newborn - Kaltsogianni, Ourania; Bhat, Ravindra; Greenough, Anne; Dassios, Theodore (Frontiers in Pediatrics, 2025)
BackgroundIt is not known whether tachycardia in persistent pulmonary hypertension of the newborn (PPHN) is due to the use of inotropic agents or is a pathophysiological process related to the disease per se. In this study, we aim to test the hypothesis that tachycardia in PPHN would be related to non-invasive indices of PPHN.MethodsThis is a retrospective study of ventilated infants with echocardiographically confirmed PPHN at the Neonatal Intensive Care Unit of King's College Hospital NHS Foundation Trust. The difference of the partial pressure of arterial (PaCO2) to end-tidal CO2 (EtCO2) or PaCO2–EtCO2 gradient was calculated as an index of PPHN severity and was related to the level of tachycardia at acute PPHN and after the resolution of PPHN (pre-extubation).ResultsFifteen infants with PPHN were studied, whose median (interquartile range, IQR) gestational age was 35.7 (34.1–40.3) weeks and birth weight was 2.95 (2.17–3.20) kg. It was found that the median (IQR) heart rate was higher during acute PPHN [158 (122–169) bpm] compared with that during pre-extubation [119 (111–136) bpm, p = 0.016]. The difference in the heart rate at acute illness and pre-extubation was significantly related to the difference in the PaCO2–EtCO2 gradient (correlation coefficient = 0.732, p = 0.016).ConclusionsThere was a significant association between tachycardia and the severity of PPHN in ventilated infants, possibly describing that tachycardia is the result of PPHN per se, as well as the effect of inotropes.